Improved Protoplast Production Protocol for Fungal Transformations Mediated by CRISPR/Cas9 in Botrytis cinerea Non-Sporulating Isolates - Víctor Coca-Ruiz; Nuria Cabrera-Gómez; Isidro G. Collado; Josefina Aleu (Plants, 2024)
Botrytis cinerea is a necrotrophic fungus that causes considerable economic losses in commercial crops. Fungi of the genus Botrytis exhibit great morphological and genetic variability, ranging from non-sporogenic and non-infective isolates to highly virulent sporogenic ones. There is growing interest in the different isolates in terms of their methodological applications aimed at gaining a deeper understanding of the biology of these fungal species for more efficient control of the infections they cause. This article describes an improvement in the protoplast production protocol from non-sporogenic isolates, resulting in viable protoplasts with regenerating capacity. The method improvements consist of a two-day incubation period with mycelium plugs and orbital shaking. Special mention is made of our preference for the VinoTaste Pro enzyme in the KC buffer as a replacement for Glucanex, as it enhances the efficacy of protoplast isolation in B459 and B371 isolates. The methodology described here has proven to be very useful for biotechnological applications such as genetic transformations mediated by the CRISPR/Cas9 tool.